Acute effects of flexible pole exercise on heart rate dynamics - Oliveira, Leticia Santana de [UNESP]; Moreira, Patricia S. [UNESP]; Antonio, Ana M. [UNESP]; Cardoso, Marco A. [UNESP]; Abreu, Luiz Carlos de; Navega, Marcelo T. [UNESP]; Raimundo, Rodrigo D.; Valenti, Vitor E. [UNESP] (Elsevier B.V., 2015)
Introduction: Exercise with flexible poles provides fast eccentric and concentric muscle contractions. Although the literature reports significant muscle chain activity during this exercise, it is not clear if a single bout of exercise induces cardiac changes. In this study we assessed the acute effects of flexible pole exercise on cardiac autonomic regulation.Methods: The study was performed on 22 women between 18 and 26 years old. We assessed heart rate variability (HRV) in the time (SDNN, RMSSD and pNN50) and frequency (HF, LF and LF/HF ratio) domains and geometric indices of HRV (RRTri, TINN, SD1, SD2 and SD1/SD2 ratio). The subjects remained at rest for 10 min and then performed the exercises with the flexible poles. Immediately after the exercise protocol, the volunteers remained seated at rest for 60 min and HRV was analyzed.Results: We observed no significant changes in time domain (SDNN: p=0.72; RMSSD: p=0.94 and pNN50: p=0.92) or frequency domain indices (LF [nu]: p=0.98; LF [ms(2)]: p=0.72; HF [nu]: p=0.98; HF [ms(2)]: p=0.82 and LF/HF ratio: p=0.7) or in geometric indices (RRTri: p=0.54; TINN: p=0.77; SD1 p=0.94; SD2: p=0.67 and SD/SD2: p=0.42) before and after a single bout of flexible pole exercise.Conclusion: A single bout of flexible pole exercise did not induce significant changes in cardiac autonomic regulation in healthy women. (C) 2014 Sociedade Portuguesa de Cardiologia. Published by Elsevier Espana, S.L.U. All rights reserved.

Introdução: Exercícios com hastes flexíveis proporcionam rápidas contrações musculares excêntricas e concêntricas. Embora a literatura relate importante ativação da cadeia muscular durante este exercício, não é claro se uma única sessão de exercício induz alterações cardíacas. Neste estudo foram avaliados os efeitos agudos da haste flexível sobre a regulação autonômica cardíaca. Métodos: O estudo foi realizado em 22 mulheres entre 18 e 26 anos. Avaliou-se a variabilidade da freqüência cardíaca (VFC) no domínio do tempo (SDNN, RMSSD e pNN50) e no domínio da frequência (HF, LF e LF relação/HF) e os índices geométricos de VFC (RRtri, TINN, SD1, SD2 e a razão SD1/SD2). Os indivíduos permaneceram em repouso por 10 minutos. Após o período de repouso, os voluntários realizaram os exercícios com as hastes flexíveis. Imediatamente após o protocolo de exercício, os voluntários permaneceram sentados em repouso por 60 minutos e a VFC foi analisada. Resultados: Não foram observadas alterações no domínio do tempo (SDNN: p=0,72; RMSSD: p=0,94 e pNN50: p=0,92) e nos índices no domínio da frequência (LF (nu): p=0,98; LF (ms2): p=0,72; HF (nu): p=0,98; HF (ms2): p=0,82 e a razão LF/HF: p=0,7), bem como para os índices geométricos (RRtri: p=0,54; TINN: p=0,77; SD1: p=0,94; SD2: p=0,67 e SD/SD2: p=0,42) entre o antes e o depois de um único exercício com haste flexível. Conclusão: Uma única sessão de exercício com vara flexível não induziu mudanças na regulação autonômica cardíaca em mulheres saudáveis. Keywords: Autonomic nervous system; Cardiovascular physiology; Exercise
Keywords: Autonomic nervous system; Cardiovascular physiology; Exercise